2023
DOI: 10.1038/s41380-022-01909-9
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion is associated with lithium response in bipolar disorder: evidence from a network-based multi-omics analysis

Abstract: Lithium (Li) is one of the most effective drugs for treating bipolar disorder (BD), however, there is presently no way to predict response to guide treatment. The aim of this study is to identify functional genes and pathways that distinguish BD Li responders (LR) from BD Li non-responders (NR). An initial Pharmacogenomics of Bipolar Disorder study (PGBD) GWAS of lithium response did not provide any significant results. As a result, we then employed network-based integrative analysis of transcriptomic and geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…A hypergeometric test found signi cant overlap (p = 5.699e-07) between the 500 gene network generated by NAGA and the 500 gene network generated by network propagation analysis in our previous study 23 . There were 33 genes that were common to both networks.…”
Section: Network Analysismentioning
confidence: 64%
See 2 more Smart Citations
“…A hypergeometric test found signi cant overlap (p = 5.699e-07) between the 500 gene network generated by NAGA and the 500 gene network generated by network propagation analysis in our previous study 23 . There were 33 genes that were common to both networks.…”
Section: Network Analysismentioning
confidence: 64%
“…In this study, we attempted to replicate our previous results which were from an independent sample 23 . We used network methods via NAGA to reprioritize GWAS results from the ConLiGen study on lithium response and used STRING to test three a priori network hypotheses: KEGG focal adhesion, ECM-receptor interaction and PI3K-Akt signaling.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We found that heterozygous knockout of AKAP11 led to upregulation of pathways such as actin-binding, calcium ion binding, SH3 domain binding, lipid binding, and PDZ domain binding, which include genes involved in cell adhesion, motility, ECM interactions, or cytoskeletal integrity--pathways that have been previously suggested to be associated with lithium response 96,97 . Moreover, we found that the upregulated genes that were linked to increased intronic enhancer activity were primarily enriched in similar pathways suggesting that intronic enhancer activity through HATs and/or HDACs, plays a role, at least in part, in such dysregulations.…”
Section: Discussionmentioning
confidence: 77%
“…underlined the direct rami cations of focal adhesion dysregulation on axon guidance and neuronal circuits. This intricate relationship might very well lay the foundation for BD's mechanistic intricacies and its amelioration upon lithium intervention [39]. Further emphasizing the role of neuronal pathways, the observed aberrancies in axon guidance hint at a potential fallout from dysregulated miRNAs present in neuron-derived exosomes from patients with BD.…”
Section: Discussionmentioning
confidence: 96%